2015
DOI: 10.1016/j.joca.2015.04.021
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of 12 weeks non-surgical treatment for patients not eligible for total knee replacement: a randomized controlled trial with 1-year follow-up

Abstract: ClinicalTrials.gov (NCT01535001).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
131
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 80 publications
(138 citation statements)
references
References 33 publications
2
131
1
4
Order By: Relevance
“…Our finding of sustained improvement in PROs during a year is in line with two recent randomized trials investigating the longterm effects of 12 weeks NEMEX 5,14 . Both studies observed continued within-group improvements at 12 or 24 months followup for the NEMEX groups.…”
Section: Patient-reported Outcomessupporting
confidence: 91%
See 1 more Smart Citation
“…Our finding of sustained improvement in PROs during a year is in line with two recent randomized trials investigating the longterm effects of 12 weeks NEMEX 5,14 . Both studies observed continued within-group improvements at 12 or 24 months followup for the NEMEX groups.…”
Section: Patient-reported Outcomessupporting
confidence: 91%
“…One-year positive effects of non-surgical interventions including NEMEX have been reported in randomized trials of patients with moderate to severe knee OA 4,5 (within-group Cohen's d ranging between 0.35 and 0.60) or in conjunction with total knee replacement 4,6,7 (within-group Cohen's d ranging between 0.47 and 0.87). One-year improvements have also been shown when NEMEX is delivered large-scale in clinical practice 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, exercise therapy was superior in improving knee-related QoL compared with self-management booklet (SMD=0.59, CI 0.16 to 1.02) 53. Exercise therapy was as effective as no treatment (SMD=0.21, CI −0.30 to 0.71) 54…”
Section: Resultsmentioning
confidence: 99%
“…Such programs have shown clinically relevant reductions in pain that last up to 5 years [10,11] and medical cost savings due to a reduced need for injections, drugs, and surgery [8], with one intervention for CKP due to knee OA showing a 75% (8/41 had knee replacement in control vs 2/42 in treatment) reduction in rate of total knee replacements [12]. Comprehensive care for CKP due to knee OA is also more effective at reducing pain in the long-term compared with physical therapy only [13-16]. However, chronic pain programs are rare for CKP, and over 80% of individuals with CKP due to knee OA receive suboptimal conservative care [17].…”
Section: Introductionmentioning
confidence: 99%